Muscle contributions to centre of mass acceleration during turning gait in typically developing children: A simulation study - Zavatsky, A; Dixon, P; Jansen, K; Jonkers, I; Stebbins, J; Theologis, T (Elsevier, 2015)
Turning while walking requires substantial joint kinematic and kinetic adaptations compared to straight walking in order to redirect the body centre of mass (COM) towards the new walking direction. The role of muscles and external forces in controlling and redirecting the COM during turning remains unclear. The aim of this study was to compare the contributors to COM medio-lateral acceleration during 90 degree pre-planned turns about the inside limb (spin) and straight walking in typically developing children. Simulations of straight walking and turning gait based on experimental motion data were implemented in OpenSim. The contributors to COM global medio-lateral acceleration during the approach (outside limb) and turn (inside limb) stance phase were quantified via an induced acceleration analysis. Changes in medio-lateral COM acceleration occurred during both turning phases, compared to straight walking (p < 0.001). During the approach, outside limb plantarflexors (soleus and medial gastrocnemius) contribution to lateral (away from the turn side) COM acceleration was reduced (p < 0.001), whereas during the turn, inside limb plantarflexors (soleus and gastrocnemii) contribution to lateral acceleration (towards the turn side) increased (p ≤ 0.013) and abductor (gluteus medius and minimus) contribution medially decreased (p < 0.001), compared to straight walking, together helping accelerate the COM towards the new walking direction. Knowledge of the changes in muscle contributions required to modulate the COM position during turning improves our understanding of the control mechanisms of gait and may be used clinically to guide the management of gait disorders in populations with restricted gait ability.